Features of HIBP diagnostics application to stellarator-like devices - Dreval, N.B.; Krupnik, L.I.; Chmyga, A.A.; Khrebtov, S.M.; Komarov, A.D.; Kozachek, A.S.; Hidalgo, C.; Melnikov, A.V.; Eliseev, L.G. (Вопросы атомной науки и техники, 2005)
Features of heavy ion beam probe application to stellarator-like devices have been connected with specific stellarator characteristics: zero (negligible) plasma current, relatively high poloidal and stray magnetic fields, toroidal asymmetry of magnetic surfaces and various operational regimes connected with different magnetic configurations. This paper shows how to decrease the errors in HIBP measurements due to these disadvantages. Absence of the plasma current in stellaratorlike devices gives possibility to make secondary ion beam energy analyzer calibration in situ in each plasma shot. This advantage improves accuracy of plasma potential measurements by HIBP diagnostic on TJ-II stellarator. Можливості застосування діагностики плазми за допомогою пучка важких іонів у пристроях стеллараторного типу зв’язанізі специфічними характеристиками стеллараторів: практично нульовий струм плазми, відносно високізначення полоідальних і розсіяних магнітних полів, тороідальна асиметрія магнітних поверхонь; і різними режимами роботи з різними магнітними конфігураціями. Показано, як можна знизити рівень похибок НІВР вимірювань, зв’язаних з цими несприятливими умовами. Відсутність струму плазми у пристроях стеллараторного типу дає можливість проводити калібровку аналізатора енергій вторинного пучка іонів у кожному плазмовому розряді. Це дозволяє збільшити точність вимірювань потенціалу плазми за допомогою пучка важких іонів на стеллараторі TJ-II. Возможности применения диагностики плазмы с помощью пучка тяжелых ионов в установках стеллараторного типа связаны со специфическими характеристиками стеллараторов: практически нулевой ток плазмы, относительно высокие значения полоидальных и рассеянных магнитных полей, тороидальная ассиметрия магнитных поверхностей; и различными режимами работы с разными магнитными конфигурациями. Показано, как можно снизить уровень ошибок HIBP измерений, вызванных этими неблагоприятными условиями. Отсутствие тока плазмы в установках стеллаторного типа дает возможность проводить калибровку анализатора энергий вторичного пучка ионов непосредственно в каждом плазменном разряде. Это позволяет увеличить точность измерения потенциала плазмы с помощью пучка тяжелых ионов на стеллараторе TJ-II.